Where Have All the Working Papers Gone? Evidence from Four Major Economics Working Paper Series - Alexandra Baumann; Klaus Wohlrabe (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Working papers or preprints have become an important part in the scientific landscape. Such papers present research before (potentially) being published in refereed journals. But is every working paper finally published in a journal? We answer this question for four major working paper series in economics. Based on linked data in RePEc and a random sample we provide an estimate of 66.5% of more than 28,000 investigated working papers that are published in a journal. About 8% are released as a book chapter. For the remaining 25.5% we find no evidence for what happened to the article.
Keywords: A12; A14; 330; working paper; journals; scholary communication; publication analysis; RePEc